Numerical study of ultra-high performance concrete under non-deformable projectile penetration. (15th March 2017) - Liu, Jian; Wu, Chengqing; Chen, Xiaowei
Highlights: Mat_72R3 is used to characterize UHPC under static and impact loadings. The DOP is investigated under various compressive strengths of UHPC, striking velocities and CRHs of projectile. The crater damage is investigated under various compressive strengths of UHPC, striking velocities and CRHs of projectile. An empirical formula is proposed to determine the DOP for UHPC. Abstract: This paper presents a numerical study in evaluating impact response of ultra-high performance concrete (UHPC) cylinder targets under ogive-nosed projectile penetration with broad striking velocities from 300 m/s to 1000 m/s. Steel ogive-nosed projectiles with an average mass of 360 g are launched to penetrate UHPC cylinder targets with 750 mm diameter and 1000 mm length. The Karagozian & Case (K&C) cementitious material model, namely, MAT_Concrete_Damage_Rel3 (Mat_72R3), is implemented into finite element package LS-DYNA for UHPC. In order to accurately predict depth of penetration (DOP) and cratering damage of UHPC cylinder targets, uniaxial compressive and four-point bending testing results are used to validate 3D finite element material model. With the validated numerical model incorporating dynamic increase factors (DIF) of UHPC, parametric studies are conducted to investigate effects of UHPC compressive strength, projectile striking velocity and projectile caliber-radius-head (CRH) ratio on both DOP and cratering damage of UHPC targets. Moreover, an empirical formula to predict DOP is derived according to the simulated data.